Allospecific Rejection of MHC Class I‐Deficient Bone Marrow by CD8 T Cells. Issue 1 (4th December 2013) - Haspot, F.; Li, H. W.; Lucas, C. L.; Fehr, T.; Beyaz, S.; Sykes, M.
Abstract Avoidance of long‐term immunosuppression is a desired goal in organ transplantation. Mixed chimerism offers a promising approach to tolerance induction, and we have aimed to develop low‐toxicity, nonimmunodepleting approaches to achieve this outcome. In a mouse model achieving fully MHC‐mismatched allogeneic bone marrow engraftment with minimal conditioning (3 Gy total body irradiation followed by anti‐CD154 and T cell–depleted allogeneic bone marrow cells), CD4 T cells in the recipient are required to promote tolerance of preexisting alloreactive recipient CD8 T cells and thereby permit chimerism induction. We now demonstrate that mice devoid of CD4 T cells and NK cells reject MHC Class I‐deficient and Class I/Class II‐deficient marrow in a CD8 T cell–dependent manner. This rejection is specific for donor alloantigens, since recipient hematopoiesis is not affected by donor marrow rejection and MHC Class I‐deficient bone marrow that is syngeneic to the recipient is not rejected. Recipient CD8 T cells are activated and develop cytotoxicity against MHC Class I‐deficient donor cells in association with rejection. These data implicate a novel CD8 T cell–dependent bone marrow rejection pathway, wherein recipient CD8 T cells indirectly activated by donor alloantigens promote direct killing, in a T cell receptor–independent manner, of Class I‐deficient donor cells.